INVENTARISASI HAMA DAN PENYAKIT PADA TANAMAN JERUK NIPIS (Citrus aurantifolia) DI DESA OELBUBUK , TIMOR TENGAH SELATAN - Agut, Oktavianus; Hahuly, Mayavira V.; Nahas, Agustina Etin; Nenotek, Petronella S. (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
This research was conducted in Oelbubuk Village, TTS Regency from October to December 2022. The purpose of this study was to determine the types of pests and causes of diseases that attack lime plants. The method used in this research is the survey method. Sampling was done by selecting villages where there are many limes. Sampling of pests is done with hands that have been coated with gloves, put into a jar containing 70% alcohol, while the diseased parts of the plant are taken stems, leaves, diseased fruit are taken and put into plastic samples and labeled, then taken to the Plant Pest Laboratory and Plant Disease Laboratory, Faculty of Agriculture, Uiversitas Nusa Cendana to be identified. The results showed that in lime plants in Oelbubuk Village, South Central Timor Regency, 6 pest species were found, namely whitefly (Bemisia tabaci), wood locust (Valanga nigricornis), leaf hopper caterpillar (Phyllocnistis citrella), snail (Caracolus marginella), mealybug (Paracoccus marginatus), leafworm (Papilio demoleus); and 4 diseases, namely leaf spot, powdery mildew, sooty mildew, and mumps/diplodia.